A New Digital Competence Framework for Primary School Design and Technology Teachers - Rozali, Mohd Zulfadli; Go, Chai Hong; Samshul, Siti Nurafiqah; Ismail, Affero; Zakaria, Anies Faziehan (Journal of Technical Education and Training, 2024)
The digital competence framework for DT teachers in primary schools was validated using Principal Component Analysis (PCA). With this framework, relevant parties identify the training needs of existing DT teachers or trainee teachers who take the DT subject for continuous self-reflection and improvement. This study was conducted to examine the reliability of the DIGIGLO Digital Competency Assessment instrument using Rasch Model as a measurement of its reliability. Testing and validation were conducted to ensure that the elements of the digital teacher competency framework meet the Principal Component Analysis (PCA) criteria. The purpose was to ensure and confirm that the measured research elements are independent. The study involved 283 primary school Design and Technology teachers in the state of Johor. Respondents answered the online questionnaire using Google Forms to obtain the necessary data for this study. For verifying the digital competency framework, the researcher used the Rasch measurement model approach by conducting Principal Component Analysis (PCA) using Winsteps software. The findings indicate that the validated framework can effectively identify areas for teacher development. Recommendations for policy and practice include targeted training programs and continuous professional development. The results indicate that the framework is reliable and effective for assessing digital competencies, and its implementation can significantly enhance the quality of DT education in primary schools in Johor. Findings of this study provides a model for precise skill assessment and tailored professional development that can be applied across various educational settings to improve vocational training. This approach ensures that TVET educators are equipped with the necessary digital skills to meet the evolving demands of the educational and labor markets, fostering a more digitally adept and competitive workforce.